Karmic Ideology in Zi Bu Yu - Aiqing Wang (Anaphora : Journal of Language, Literary, and Cultural Studies, 2026)
Zi Bu Yu ‘What the Master Would not Discuss’ or ‘Censored by Confucius’ is a zhiguai ‘strange writing’ anthology compiled during the Qing (1644-1912) era, which concerns supernatural and divine phenomena, occurrences as well as flora and fauna. Zi Bu Yu also pertains to a karmic construct from an ethical-religious perspective by virtue of interconnection to Confucianism and Taoism. Although narratives collected in Zi Bu Yu defy Confucian atheism, they depict well-deserved nemeses manifesting Confucian symmetrical reciprocity. In terms of Taoism, it is embodied by recompenses recounted in Zi Bu Yu, as well as its similitude to the Confucian precept of benevolence. Furthermore, tales cumulated in Zi Bu Yu expound the rationale behind cause and effect as well as reward and punishment, by means of illuminating justifiable and ostensibly unjustifiable karma in a philosophical manner.